The Influence of Word-of-Mouth Communication on Purchasing Decisions for Depot Dua Legenda Food Products in Malang City - Novi Ratriningtyas; Purnomo, Agung; Erfaridiansyah, Niazi (International Journal of Multidisciplinary Applied and Science Research, 2024)
The increasingly competitive culinary business landscape demands that entrepreneurs adopt effective and efficient marketing strategies. Among various available strategies, Word of Mouth (WOM) communication has proven to be one of the main drivers of consumer purchasing decisions due to its honest, personal, and trustworthy nature. This study aims to analyze and measure the extent of the influence of WOM communication on consumer purchasing decisions, using Depot Dua Legenda as a case study—a contemporary culinary business with a unique concept in Malang City. This research employs an explanatory quantitative approach using a survey method. A sample of 100 consumers of Depot Dua Legenda was selected using purposive sampling technique. Data were collected through questionnaires using a 4-point Likert scale and analyzed using descriptive and inferential statistical analysis, including validity testing, reliability testing, Pearson correlation, and linear regression. The research findings indicate that Word of Mouth communication has a positive and significant influence on the purchasing decisions of consumers at Depot Dua Legenda. A correlation coefficient of 0.708 indicates a strong relationship between the two variables. The regression analysis results produce the equation Y = 7.072 + 0.565X, meaning that every one-unit increase in WOM increases purchasing decisions by 0.565 units. Furthermore, the WOM variable can explain 50.1% of the variation in purchasing decisions (R Square = 0.501). This finding reinforces the statement that WOM, especially when organic and amplified through digital media, plays a primary role in driving consumer decision-making processes in the modern era.